2013
DOI: 10.1053/j.ajkd.2013.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Association of Income Level With Kidney Disease Severity and Progression Among Children and Adolescents With CKD: A Report From the Chronic Kidney Disease in Children (CKiD) Study

Abstract: Background Among adults, lower socioeconomic status (SES) is a risk factor for chronic kidney disease (CKD), progression to end stage renal disease, and poor health outcomes, but the effect among young people with CKD is not well known. Study Design Prospective cohort study. Settings & Participants 572 children and adolescents aged 1 to 16 years with mild to moderate CKD residing in the United States and Canada who were enrolled in the Chronic Kidney Disease in Children (CKiD) Study, a multicenter prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 19 publications
(16 reference statements)
1
34
0
Order By: Relevance
“…This evaluation should focus on identified risk factors, such as ipsilateral CAKUT, small renal size, low birth weight, prematurity, and history of urinary tract infection. In addition, the Chronic Kidney Disease in Children cohort study has identified clinical (anemia, hyperphospatemia, and short stature) (50) and socioeconomic (lower income and lower maternal education) (51) risk factors that are associated with the development of CKD in children, including solitary functioning kidney patients. Risk assessment also requires imaging techniques, such as renal ultrasound, in all patients and on indication, renal scintigraphy and/or a micturating cystourethrogram (for additional CAKUT including VUR) together with repeated follow-up of renal length.…”
Section: Discussionmentioning
confidence: 99%
“…This evaluation should focus on identified risk factors, such as ipsilateral CAKUT, small renal size, low birth weight, prematurity, and history of urinary tract infection. In addition, the Chronic Kidney Disease in Children cohort study has identified clinical (anemia, hyperphospatemia, and short stature) (50) and socioeconomic (lower income and lower maternal education) (51) risk factors that are associated with the development of CKD in children, including solitary functioning kidney patients. Risk assessment also requires imaging techniques, such as renal ultrasound, in all patients and on indication, renal scintigraphy and/or a micturating cystourethrogram (for additional CAKUT including VUR) together with repeated follow-up of renal length.…”
Section: Discussionmentioning
confidence: 99%
“…There is a perception that shorter children may be more motivated to take rhGH because of peer concerns; however, this was not supported by our data, because there was no difference in nonadherence among those with height z scores#3rd percentile versus .3rd percentile. More detailed analysis of the possible association between socioeconomic status, medication nonadherence, and growth is warranted, especially in light of the recent data regarding linear growth in children of low socioeconomic status (30,31). Analysis of parental and patient self-perceived barriers to adherence may provide additional clues and help to develop an effective intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Since lower socioeconomic status (SES) was associated with AA race in this North American cohort, and low SES is associated with disease progression (20), SES is a potential confounder as the exposure groups largely differ by race. To adjust for confounding due to SES, we used inverse probability of exposure weights (IPWs) (21, 22).…”
Section: Methodsmentioning
confidence: 99%